Understanding the impacts of septicity on wastewater treatment - Mendizabal Bengoetxea, Julen (Cranfield University, 2022)
Wastewater septicity develops during wastewater conveyance through the sewerage network to the wastewater treatment plant (WWTP). The problems related to septicity have been mainly researched in sewerage networks and are almost exclusively related to hydrogen sulphide, such as concrete corrosion and odour nuisance. The aim of this work is to better understand the mechanisms governing septicity in wastewater and mitigate the impacts both in sewers and wastewater treatment plants. For doing so, a septicity measure that captures the key indicators was developed, which include sulphide, oxidation reduction potential (ORP), pH, soluble COD and ammonia. Furthermore, the impacts of septicity on a conventional wastewater treatment plant consisting of a primary settler, activated sludge plant and secondary settler were tested. Septic wastewater with 6.4 mg/L of sulphide was found to impact activated sludge flocs, with significant proliferation of filamentous bacteria, resulting also in a reduced COD removal by 55% and nitrification by 44%. Furthermore, sludge bulking in the secondary settler and consequent biomass washout was observed. Additionally, the impact on chemical phosphorus removal (CPR) was tested and septic wastewater was found to reduce the effectiveness of CPR starting at a 0.35 S:Fe molar ratio and only 10% phosphorus removal efficiency was measured at a 1.4 S:Fe molar ratio. Finally, a novel dissolved sulphide sensor was trialled to monitor sulphide at the inlet chamber of a WWTP. The data collected allowed the assessment of the efficiency of nitrate dosing at a rising main. Furthermore, it allowed to build up a data-driven sulphide prediction model utilising readily available data. Overall, the thesis provided the starting bricks for the development of a septicity management framework and highlighted that optimised nitrate dosing at the study rising main utilising the dissolved sulphide data was the most economic septicity management option.
Bajon Fernandez, Yadira - Associate Supervisor
Keywords: Sewer; hydrogen sulphide; sulphate reducing bacteria; corrosion; activated sludge; chemical phosphorus removal; calcium nitrate; sulphide sensor; inhibition; bulking